2017
DOI: 10.1080/14767058.2016.1272567
|View full text |Cite
|
Sign up to set email alerts
|

Can AMH levels predict the need for increased medication during IVF/ICSI in PCOS women?

Abstract: PCOS with AMH >4.6 ng/ml are resistant to HMG stimulation, require dose step up during ART cycles, and are at higher risk for severe OHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
2
11
0
1
Order By: Relevance
“…Our results are consistent with previous researches done by Amer et al in 2013[21] and by Ahmed Kamel et al in 2017 [14]. Both of them showed that PCOS with markedly raised circulating AMH were resistant to HMG stimulation and might require a higher starting dose.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous researches done by Amer et al in 2013[21] and by Ahmed Kamel et al in 2017 [14]. Both of them showed that PCOS with markedly raised circulating AMH were resistant to HMG stimulation and might require a higher starting dose.…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that PCOS patients with higher serum AMH levels have a lower possibility of response to clomiphene or LET [ 23 ]. Besides, high serum AMH levels are associated with a significantly lower probability of response to human menopausal gonadotrophin stimulation [ 24 , 25 ]. High AMH is associated with lower live birth rates in women with PCOS undergoing assisted reproductive technology [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 They were associated with gonadotrophin dosages and risks of severe OHSS in PCOS patients undergone IVF. 23 So people proposed AMH as one of the factors related to the degree of severity of PCOS. 24 Follicular fluid is the site for oocyte growth and development.…”
Section: Discussionmentioning
confidence: 99%